Foreign Body in Jugal Mucosa - Serrano, Thiago Luís Infanger; Pauna, Henrique Furlan; Hazboun, Igor Moreira; Dal Rio, Ana Cristina; Correa, Maria Elvira Pizzigatti; Nicola, Ester Maria Danielli (International Archives of Otorhinolaryngology, 2015)
Introduction Foreign body in the oral cavity may be asymptomatic for long time and only sometimes it can lead to a typical granulomatous foreign body reaction. Some patients may complain of oral pain and present signs of inflammation with purulent discharge. A granuloma is a distinct, compact microscopic structure composed of epithelioid-shaped macrophages typically surrounded by a rim of lymphocytes and filled with fibroblasts and collagen. Nowadays, the increase of cosmetic invasive procedures such as injection of prosthetic materials in lips and cheeks may lead to unusual forms of inflammatory granulomas.Objectives Describe an unusual presentation of a foreign body reaction in the buccal mucosa due to previous injection of cosmetic agent.Resumed Report A 74-year-old woman was referred to the Department of Otorhinolaryngology, Head and Neck Surgery to investigate the presence of multiple painless, bilateral nodules in the buccal mucosa, with progressive growth observed during the previous 2 months. The histologic results showed a foreign body inflammatory reaction.Conclusion Oral granulomatosis lesions represent a challenging diagnosis for clinicians and a biopsy may be necessary. Patients may feel ashamed to report previous aesthetic procedures, and the clinicians must have a proactive approach.
Keywords: foreign body reaction; granulomatosis; orofacial; differential diagnoses; esthetic surgery